Does Commonality in Illiquidity Matter to Investors? - Richard G. Anderson; Jane M. Binner; Björn Hagströmer; Birger Nilsson (Lund University, School of Economics and Management, Department of Economics, 2013)
This paper investigates whether investors are compensated for taking on commonality risk in equity portfolios. A large literature documents the existence and the causes of commonality in illiquidity, but the implications for investors are less understood. We find a return premium for commonality risk in NYSE stocks that is both economically and statistically signi cant. The commonality risk premium is independent of illiquidity level effects, and robust to variations in illiquidity measurement and systematic illiquidity estimation. We also show that precision in commonality risk estimation can be increased by the use of daily illiquidity measures, instead of monthly.
Keywords: G11; G12; 330; commonality; commonality risk premium; asset illiquidity; systematic illiquidity; liquidity; effective tick